2014
DOI: 10.1007/s00018-014-1669-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase-producing oral mitis group streptococci potentially contribute to influenza viral infection and reduction in antiviral efficacy of zanamivir

Abstract: Influenza is a serious respiratory disease among immunocompromised individuals, such as the elderly, and its prevention is an urgent social issue. Influenza viruses rely on neuraminidase (NA) activity to release progeny viruses from infected cells and spreading the infection. NA is, therefore, an important target of anti-influenza drugs. A causal relationship between bacteria and influenza virus infection has not yet been established, however, a positive correlation between them has been reported. Thus, in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…mitis group species are important colonizers of the oral cavity, and are occasionally associated with serious infections [ 15 ]. In addition, these organisms have recently been suggested to play important roles in the pathogenesis of influenza [ 8 ]. Therefore, the genomic study of diverse S .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…mitis group species are important colonizers of the oral cavity, and are occasionally associated with serious infections [ 15 ]. In addition, these organisms have recently been suggested to play important roles in the pathogenesis of influenza [ 8 ]. Therefore, the genomic study of diverse S .…”
Section: Resultsmentioning
confidence: 99%
“…mitis were found to produce neuraminidase (NA), a vital target of anti-influenza drugs. The NA activity exhibited by these oral bacteria stimulates the release of influenza virus, boosts viral M1 protein expression levels and activates the cell signaling ERK pathway, potentially enhancing viral infections [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the number of S. mitis cases could also have hampered the efficacy of the viral neuraminidase inhibitor drug. 21 Of the four H1N1 patients who died, S. mitis was present in three.…”
Section: Discussionmentioning
confidence: 97%
“…The 8-month-old male had eight symptoms and harbored S. mitis , which could have elevated the risk of and exacerbated the influenza infection. 21 …”
Section: Discussionmentioning
confidence: 99%
“…NA, an envelope glycoprotein on the surface of the influenza virus, catalyses the cleavage of sialic acids on glycoproteins from virus-infected cells and enables virus release [18, 19]. Studies have demonstrated that low NA enzyme activity renders virus release from infected cells inefficient and leaves progeny viruses gathered on the cell surface [19, 20]. DCs represent a central element in the generation and maintenance of immune responses [21].…”
Section: Discussionmentioning
confidence: 99%